Kinematic differences between sprinting and the hurdle jump exercise - a preliminary analysis - Healy, R.; Bolger, R.; Kenny, I. C.; Harrison, A. J. (ISBS Proceedings Archive (Michigan), 2020)
The hurdle jump is a commonly prescribed plyometric exercise for sprint athletes. The purpose of this study was to assess the lower body kinematic differences between maximal velocity sprinting and hurdle jumps performed over a range hurdle heights. Six competitive male sprinters performed maximum effort sprints over 50 m and hurdle jumps over 0.60, 0.75 and 0.90 m. Ground contact times, ankle, knee, and hip angles were collected during the ground contact phase of all trials. Significantly lower peak dorsiflexion angles and lower mean ground contact times were found in sprinting compared to all three hurdle jump conditions (all p < 0.015). The hurdle jump exercise may be a suitable exercise for sprint athletes due to the greater demand imposed on the athlete relative to maximum velocity sprinting. Coaches are advised to monitor ground contact times to ensure the intensity of the exercise is not excessive.